2022
DOI: 10.1111/apa.16576
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 increased in Italian children in the autumn and winter 2021–2022 period when Omicron was the dominant variant

Abstract: Aim: We examined the prevalence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in children during the autumn and winter season from 1 September 2021 to 30 January 2022 and compared it with the same period in 2020-2021. Methods: This study was carried out int the paediatric emergency department (PED) of a tertiary Italian hospital. We compared the clinical and demographical features of all children who presented during the two study periods and tested positive for SARS-CoV-2. Results: Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…We showed a peak in November–December in Group B (post-pandemic), while in Group A (pre-pandemic), the peak was reached in January–February. This confirms new epidemiological trends of HRSV infection as reported worldwide [ 18 , 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…We showed a peak in November–December in Group B (post-pandemic), while in Group A (pre-pandemic), the peak was reached in January–February. This confirms new epidemiological trends of HRSV infection as reported worldwide [ 18 , 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Lachassinne et al [ 87 ] also found in their seroprevalence studies in French day care centres that the share of SARS-CoV-2 infections in young children was low. However, recent studies have shown that the continuation of the epidemic with new SARS-CoV-2 variants and shifts in preventive measures and vaccination changed the situation [ [88] , [89] , [90] , [91] ]. In addition, it seems that transmission between family members seemed more important than transmission within day care centres [ 87 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 The increase in severity of illness could also be due to a greater virulence of circulating RSV. 10 Cord RSV IgG antibody level is related with disease severity in the first six months. 11 Decreased encounters of pregnant women with RSV due to COVID-19 appropriate behavior may have resulted in an inherently less passive immunity against the virus in their newborns leaving them susceptible to potentially severe RSV illness.…”
Section: Discussionmentioning
confidence: 99%